1997
DOI: 10.1113/expphysiol.1997.sp004068
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of fusimotor reflex responses during locomotion in the decerebrate cat

Abstract: SUMMARYThe effect of brief trains of electrical stimulation, at 2, 3 and 20 x threshold (T), of cutaneous afferents in the medial plantar nerve on the discharges of single medial gastrocnemius static and dynamic y-efferents has been investigated at rest and during locomotion in a decerebrate cat preparation. The units were classified as dynamic (10 units) or static (10 units) indirectly on the basis of their resting and locomotor discharge characteristics. Responses were assessed by calculating the change in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…It also means that the input鈥搊utput relationship seen in one condition may even reverse if the context or state of the system is altered. Fusimotor reflex reversal has been demonstrated during walking in the cat (Murphy & Hammond, 1997) and this principle of motor control is well known (Lacquaniti et al 1991; De Serres et al 1995). This notion would also fit with the suggestion that muscle spindles represent the final step in an integrative network which joins information from muscle, skin and joint receptors (Johansson, 1985).…”
Section: Discussionmentioning
confidence: 96%
“…It also means that the input鈥搊utput relationship seen in one condition may even reverse if the context or state of the system is altered. Fusimotor reflex reversal has been demonstrated during walking in the cat (Murphy & Hammond, 1997) and this principle of motor control is well known (Lacquaniti et al 1991; De Serres et al 1995). This notion would also fit with the suggestion that muscle spindles represent the final step in an integrative network which joins information from muscle, skin and joint receptors (Johansson, 1985).…”
Section: Discussionmentioning
confidence: 96%
“…The initial mechanism with regard to the enhancement of muscle strength and muscle control is that cutaneous fusimotor reflex increases fiber tension, resulting in excitation of primary and secondary nerve endings, thus, helping afferent sensory nerve activity 23 , 24 ) . The mechanism of taping is improvement of muscle strength by excitation of gamma motor nerves in skeletal muscle, as the taped part raises the tension of the fiber 25 , 26 ) . In addition, spatial summation makes neurotransmitter isolated and postsynaptic potential is generated without action potential of pre-synaptic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity (EMG) of those muscles is more pronounced during the unstretched phase. Therefore, dynamic and phase-dependent control of the CPG on muscle spindle sensitivity through alpha-gamma co-activation is very important for stabilization of the gait (Murphy and Hammond 1997;Taylor et al 2000;Windhorst 2007). In addition, alpha-gamma co-activation varies with the task as well (Prochazka 1989;Rossignol et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Duenas et al (1990) showed clear evidence for a phase dependency of the monosynaptic reflex during locomotion in the cat. The action of some of the reflex mechanisms, for instance fusimotor drive for the ankle extensor of the cat hindlimb (Murphy and Hammond 1997), could get reversed depending on the phase of the walking leg. Therefore, the system level analysis of the muscle-joint interactions at several positions throughout the step cycle will give more insight into the understanding of the controllability and the stability of the locomotion.…”
mentioning
confidence: 99%